PENGARUH KELENGKAPAN ADMINISTRASI DAN KATEGORI IMPORTIR TERHADAP DWELLING TIME PADA PT. ANUGERAH INDO MARITIM SEJAHTERA MEDAN BELAWAN - Nadila Arum Ningsih; Sahnan Rangkuti; Mierna Zulkarnain (Universitas Dharmawangsa, 2022)
To ensure imports, or organizations must comply with regulations by the Department of Immigration and External Border Protection of the State and customs. This study aims to determine the effect of administrative completeness and importer category on Dwelling Time at PT. The Indo Maritime Prosperity Award in Medan Belawan. The results showed that the t-test on administrative completeness had a negative effect on residence time. In this regard, the exporter is not careful in issuing commercial invoices and packing lists as filling in the PIB by PT AIMS. The import category based on the t-test has an effect or is in the direction of residence time. In this regard, the OSS application made by the government as a registration requirement in the issuance of API, NIK, NPWP related to the importer category has not been well integrated. The general importer category can only have one API-U for each imported item. The requirements for tax rates for the import category are limited, high tariffs make companies (customers) delay payment of import taxes to the state treasury. In the single agent importer category, quota restrictions for imports of factory-produced goods abroad are an obstacle because goods that are almost at the port due to the new enactment of this regulation make imported goods enter the customs inspection lane because they exceed the quota for imported goods. In the determination test, administrative completeness and importer category only affected 20.2% of residence time and the remaining 79.8% of other factors not examined.